PEMETAAN SOSIAL MASYARAKAT PESISIR UNTUK MENDUKUNG PENGELOLAAN PERIKANAN BERKELANJUTAN DI TWP PADAIDO KABUPATEN BIAK NUMFOR - SUDIRMAN ADIBRATA (Akuatik: Jurnal Sumberdaya Perairan, 2012)
Social mapping of coastal communities in TWP Padaido was expected to provide a preliminary picture of the living conditions of the communities in coral reef management priorities location of COREMAP program. This study seeks to collect informations mainly from the focus group discussion (FGDs) and the study of literature both in Biak Numfor and Jakarta. The findings showed that “the three furnace system” e.g. the role of traditional leaders, churches, and government agencies are very dominant in influencing fisheries management rules. In TWP Padaido, the government through the program COREMAP primarily involved in providing policy support for implementing local regulations. In general, traditional systems have a positive impact on society such as sasi. This system can avoid disputes in the resources uses and provide a better incomes for fishermen in TWP Padaido.